PENINGKATAN PARTISIPASI ORANGTUA PESERTA DIDIK BERBASIS TEKNOLOGI INFORMASI - Argamas Viki Putra Malindo; Ali Imron; Raden Bambang Sumarsono (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstrak: This study aims to describe (1) the Go Application management process. (2) parental understanding in using Go Application as a forum for participation. (3) the impact of using Go Applications for schools and parents of students. (4) supporting factors in using Go Applications (5) inhibiting factors in using Go Applications and their solutions. (6) handling of obstacles in the use of Go Application. The research method used is qualitative, with a case study design in SMP Negeri 3 Malang. Data collected using observation techniques, in-depth interviews, and documentation. As for data analysis using a single case analysis technique. The results of this study include (1) the process of managing Go Applications including activities from planning, organizing, implementing, and evaluating. (2) parental understanding in using Go Application as a place of participation can facilitate the work of parents and schools, the existence of communication, and parents participate. (3) the positive impact of Go Applications, namely that school members are encouraged to use IT, assisted the learning process, is easy and shortens the time. Meanwhile, for the negative impact, the implementation process requires time and the use of mobile phones that do not fit the corridor. (4) supporting factors in the use of Go Application to increase the participation of students' parents by the potential of the school which includes the principal, the IT team, teachers, committees, parents, and students. (5) inhibiting factors in the use of Go Application and the solution there are passive parents, busy parents and there is a solution in the presence of communication and coming to school. (6) handling of obstacles in the use of Go Application by motivating, adding variety, having training, and appealing.Keywords: improvement, parental participation, information technologyAbstrak: Penelitian ini bertujuan untuk mendeskripsikan (1) proses pengelolaan Go Aplikasi. (2) pemahaman orangtua dalam penggunaan Go Aplikasi sebagai wadah partisipasi. (3) dampak penggunaan Go Aplikasi bagi sekolah dan orangtua peserta didik. (4) faktor pendukung dalam penggunaan Go Aplikasi (5) faktor penghambat dalam penggunaan Go Aplikasi dan solusinya. (6) penanganan atas hambatan dalam penggunaan Go Aplikasi. Metode penelitian yang digunakan adalah kualitatif, dengan desain studi kasus di SMP Negeri 3 Malang. Data yang dikumpulkan menggunakan teknik observasi, wawancara mendalam, dan dokumentasi. Adapun untuk analisis data menggunakan teknik analisis kasus tunggal. Hasil penelitian ini meliputi (1) proses dalam pengelolaan Go Aplikasi meliputi kegiatan dari perencanaan, pengorganisasian, pelaksanaan, dan evaluasi. (2) pemahaman orangtua dalam penggunaan Go Aplikasi sebagai wadah partisipasi terdapat memudahkan pekerjaan orangtua dan sekolah, adanya komunikasi, dan orangtua berpartisipasi. (3) dampak positif adanya Go Aplikasi, yaitu warga sekolah terpacu menggunakan IT, terbantunya proses pembelajaran, mudah dan mempersingkat waktu. Sementara itu untuk dampak negatif adalah proses implementasinya membutuhkan waktu dan penggunaan handphone yang tidak sesuai koridor. (4) faktor pendukung dalam penggunaan Go Aplikasi untuk meningkatkan partisipasi orangtua peserta didik dengan adanya potensi sekolah yang meliputi kepala sekolah, tim TI, guru, komite, orangtua, dan siswa. (5) faktor penghambat dalam penggunaan Go Aplikasi dan solusinya terdapat orangtua yang pasif, kesibukan orangtua dan terdapat solusi dengan adanya komunikasi dan datang ke sekolah. (6) penanganan atas hambatan dalam penggunaan Go Aplikasi dengan memotivasi, menambah variasi, adanya pelatihan, dan himbauan.Kata Kunci: peningkatan, siswa, teknologi informasi